Deprescribing in Older Adults With Cardiovascular Disease - Krishnaswami, Ashok; Steinman, Michael A; Goyal, Parag; Zullo, Andrew R; Anderson, Timothy S; Birtcher, Kim K; Goodlin, Sarah J; Maurer, Mathew S; Alexander, Karen P; Rich, Michael W; Tjia, Jennifer (Journal of the American College of Cardiology, 2019)
Deprescribing, an integral component of a continuum of good prescribing practices, is the process of medication withdrawal or dose reduction to correct or prevent medication-related complications, improve outcomes, and reduce costs. Deprescribing is particularly applicable to the commonly encountered multimorbid older adult with cardiovascular disease and concomitant geriatric conditions such as polypharmacy, frailty, and cognitive dysfunction-a combination rarely addressed in current clinical practice guidelines. Triggers to deprescribe include present or expected adverse drug reactions, unnecessary polypharmacy, and the need to align medications with goals of care when life expectancy is reduced. Using a framework to deprescribe, this review addresses the rationale, evidence, and strategies for deprescribing cardiovascular and some noncardiovascular medications.